ICT-driven development and the 2022-23 Union Budget of India - Nirupam Bajpai; John Biberman (Columbia University, Earth Institute, Center for Sustainable Development (CSD), 2022)
The Government of India released its 2022 Union Budget on February 1, 2022. The new budget has drawn substantial attention for, among other things, its emphasis on programs in the domain of ICT-driven development. If the ambitions described within the budget are fully realized, they would allow India to make substantial progress in equitable human development. However, the budget does not detail the funding mechanisms that would support these ambitious programs, and similar efforts have floundered in the past due to this lack of specificity. If India intends to promote ICT-driven development at the central level through its budget, then these documents should provide states and ministries concrete information on the dedicated revenue flows they will have at their disposal so that they can proceed with these initiatives in a timely and efficient manner.
Keywords: 330; Öffentlicher Haushalt; Digitalisierung; Entwicklung; Indien